2013
DOI: 10.1002/aqc.2422
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying morphological and genetic variation of sympatric populations to guide conservation of endangered, micro‐endemic springsnails

Abstract: The endangered snails Juturnia kosteri and Pyrgulopsis roswellensis are endemic to springs on Bitter Lake National Wildlife Refuge, NM, USA. These species are small and difficult to distinguish by shell shape. A morphological analysis of these two species was conducted using geometric morphometrics, and a phylogenetic analysis using the mitochondrial DNA genes COI and ND1 was performed. Principal component analysis showed significant overlap in shell shape between the two species. Phylogenetic analysis showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Chihuahuan Desert springs are known to harbour a large number of endemic species, many of which are cryptic, making it difficult to assess biodiversity accurately. Recently, DNA barcoding and other molecular delimitation techniques have revealed a high degree of cryptic diversity in fishes (Echelle et al, ; Echelle & Echelle, ), snails (Hershler, Liu, & Howard, ; Morningstar et al, ), and amphipods (Adams et al, ; Cannizzaro, Walters, & Berg, ; Seidel et al, ). In this study, phylogenetic and species delimitation analyses both found that planaria inhabiting springs of the northern Chihuahuan Desert are likely to include many undescribed species or extant species whose reference genetic data were not included in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chihuahuan Desert springs are known to harbour a large number of endemic species, many of which are cryptic, making it difficult to assess biodiversity accurately. Recently, DNA barcoding and other molecular delimitation techniques have revealed a high degree of cryptic diversity in fishes (Echelle et al, ; Echelle & Echelle, ), snails (Hershler, Liu, & Howard, ; Morningstar et al, ), and amphipods (Adams et al, ; Cannizzaro, Walters, & Berg, ; Seidel et al, ). In this study, phylogenetic and species delimitation analyses both found that planaria inhabiting springs of the northern Chihuahuan Desert are likely to include many undescribed species or extant species whose reference genetic data were not included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol and formalin are the most popular reagents for long‐term preservation of field samples (Carter & Resh, ), with ethanol preservation preferred over formalin when samples are to be used for molecular analyses and DNA barcoding (Stein, White, Mazor, Miller, & Pilgrim, ). The current study was part of a biodiversity assessment of benthic macroinvertebrates in the springs of the northern Chihuahuan Desert (Adams et al, ; Ansah, Inoue, Lang, & Berg, ; Cannizzaro et al, ; Gervasio, Berg, Lang, Allan, & Guttman, ; Holste, Inoue, Lang, & Berg, ; Morningstar et al, ; Sei, Lang, & Berg, ; Seidel et al, ; Stanislawczyk et al, ); therefore, quantitative sampling followed by ethanol preservation was conducted. However, ethanol preservation methods are known to fade the coloration of body pigments (Morningstar et al, ) and cause contraction and twisting of soft bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each spring system investigated contained a distinct community composed of many unique species, including several federally endangered species of hydrobiid snails and amphipods. Many of these microendemic taxa are restricted globally to single springs or groundwater systems (Hershler, Liu, & Landye, ; Morningstar, Inoue, Sei, Lang, & Berg, ). Identifications in the present study were limited by taxonomic resolution and distribution data for the region.…”
Section: Discussionmentioning
confidence: 99%
“…Locally dense aggregations occur in perennial aquatic habitats (Brown et al , ). Because perennial surface waters are often groundwater‐dependent and isolated from one another, springsnail species occupy geographically narrow ranges, often consisting of a single spring or spring complex (Taylor, ), and thus are vulnerable to extinction caused by human activity (Hershler et al , ; Morningstar et al , ). For example, about 80% of 130 species in the genus Pyrgulopsis are considered endangered (G1 status) by NatureServe and the International Union for Conservation of Nature (Johnson et al , ; Hershler et al , ).…”
Section: Introductionmentioning
confidence: 99%